2007
DOI: 10.1089/jop.2006.0149
|View full text |Cite
|
Sign up to set email alerts
|

Local Tolerance and Systemic Safety of Pegaptanib Sodium in the Dog and Rabbit

Abstract: These studies, together with data from clinical trials, provide strong evidence that inhibition of VEGF(165) by pegaptanib in the eye is a safe therapy for the treatment of ocular neovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 22 publications
0
28
0
2
Order By: Relevance
“…They can also undergo reversible denaturation, making them a very versatile tool for drug loading and antidote applications (Bompiani et al, 2012). Moreover, aptamers elicit little to no immunogenicity in therapeutic applications (Eyetech Study Group, 2002;Foy et al, 2007;Zhu et al, 2012). Furthermore, many functional groups and/or nucleotide extensions can be introduced onto aptamers.…”
Section: Introductionmentioning
confidence: 99%
“…They can also undergo reversible denaturation, making them a very versatile tool for drug loading and antidote applications (Bompiani et al, 2012). Moreover, aptamers elicit little to no immunogenicity in therapeutic applications (Eyetech Study Group, 2002;Foy et al, 2007;Zhu et al, 2012). Furthermore, many functional groups and/or nucleotide extensions can be introduced onto aptamers.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Clinical studies have shown that the inhibition of VEGF by intravitreal pegaptanib sodium results in the stabilization or improvement of vision in patients with neovascular ARMD; and, unlike bevacizumab, it has been produced for intraocular application. 15,18 -20 However, there are limited preclinical studies associated with the intravitreal administration of pegaptanib sodium in vivo 21 and in vitro. 10,12 In our previous study, we investigated early and late-term retinal toxicity of bevacizumab by light and electron microscopic study in rabbit eyes and found ultrastructural changes in the mitochondria in the inner segments of the photoreceptors, suggesting increased apoptotic activity.…”
mentioning
confidence: 99%
“…In a systemic safety study in dogs and rabbits involving intravitreal pegaptanib doses up to 10 times the approved clinical dose as well as bolus intravenous pegaptanib injections, no clinical, ophthalmologic, pathologic or cardiovascular abnormalities were observed. 73 Similarly, no systemic signals were detected in the safety/pharmacokinetic trial in which patients treated intravitreally for AMD received up to 10 times the clinical dose for 1 year. 37 There was no evidence of an impact of pegaptanib treatment on blood pressure or urinary protein.…”
Section: Safety Studies With Pegaptanibmentioning
confidence: 98%